Macrocheles muscaedomesticae (Acari, Macrochelidae) and a species of Uroseius (Acari, Polyaspididae) phoretic on Musca domestica (Diptera, Muscidae): effects on dispersal and colonization of poultry manure - Rodrigueiro,Tatyana Sacchi Carmona (2004)
Differences in the phoresy of the mites Macrocheles muscaedomesticae (Scopoli, 1972) (Macrochelidae) and Uroseius sp. (Polyaspidae) on the house fly, Musca domestica (Linnaeus, 1758) and the similarities in their phoretic dispersal and parasitism are discussed, altogether with the effects on predator-prey interactions. The prevalence and intensity of phoresy in the mite species were significantly related to the attachment site on the hosts. The phoresy of Uroseius sp. was correlated with temperature but not with rainfall and relative humidity. Selective pressure in the environment resulted in displacement and the emergence of local and regional populations. These results suggest that in each habitat the populations will use different resources and will show several relationships with other species, as well as a selection for morphological and behavioral types.